Sustainable public procurement practice: a study on Bangladesh Institute of Capital Market - Monir, Md. Murad Alam (Brac University, 2024)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2023.